Srovnání výsledků operační léčby rhizartrózy metodou interpoziční artroplastiky dle Burtona-Pellegriniho a implantací trapeziometakarpální endoprotézy - Jurča, J; Němejc, M; Havlas, V (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2016)
PURPOSE OF THE STUDY: The aim of the study was to compare results of the Burton-Pellegrini trapeziectomy with ligamentoplasty using the flexor carpi radialis tendon with those of trapeziometacarpal joint replacement in the treatment of advanced rhizarthrosis. MATERIAL AND METHODS: A group of 17 patients, 15 men and two women, underwent trapeziectomy with ligamentoplaty; in 12 of them, the dominant hand was involved. The trapeziometacarpal joint prosthesis Beznoska was implanted in 11 patients (10 men and one woman) with seven dominant and four non-dominant hands. All patients pre-operatively experienced pain during thumb movement and hand grip. They were examined before surgery and at 3, 6 and 12 months after it; the values obtained before and at 1 year after surgery were compared. The methods of evaluation included pain intensity assessed using the visual analogue scale (VAS), the Kapandji thumb opposition test and the disabilities of the arm, shoulder and hand (DASH) score (total DASH score and its thumb-targeted module). RESULTS: In the group treated by the Burton-Pellegrini procedure, the average pre- and post-operative Kapandji scores were 6.4 and 8.9, respectively. The average VAS scores were 5/10 pre-operatively and 1/10 post-operatively. The average values for the total pre- and post-operative DASH scores were 58 and 19 points, respectively. The DASH score in a thumb-targeted module assessing basal joint-loading in the thumb was 63 points before and 21 points after surgery. In the patients with total joint replacement, the average pre- and post-operative values were as follows: Kapandji score, 7.4 and 9.8; VAS score, 5/10 and 1/10; total DASH score, 56 and 7 points; thumb module DASH score, 60 and 11 points. Two serious complications were recorded, an infection in resection interposition arthroplasty and a trauma associated with total joint replacement loosening. Four patients showed transient paresthesia. DISCUSSION: Several methods for surgical treatment of rhizarthrosis are available today. Arthrodesis is still a widely used procedure although it inhibits thumb movements. Resection arthroplasty provides sufficient pain-free thumb motion, but radial shortening and a loss of grip strength are its disadvantages. Resection interposition arthroplasty results in sufficient painless motion. Tendon interposition provides enough stability for the thumb and for sufficient grip and pinch strength. The disadvantages of this method include a potential for failure of the suspensory tendon during over exercising or a weakened attachment of the autologous tendon to the bone and thus a risk of rupture. Total joint replacement respects the thumb anatomy, preserves the articular capsule and fibrous structures during conservative resection of joint surfaces and keeps the biomechanics of the basal joint of the thumb. It combines advantages of the other surgery procedures, by allowing for a painless range of motion in the joint and vital pinching and gripping abilities, while avoiding their disadvantages such as movement restriction and loss of grip strength. However, the technique may still bear any of the risks associated with foreign material implantation (dislocation, replacement failure, infection, etc.). CONCLUSIONS: The two techniques present valuable contributions to the treatment of advanced rhizarthrosis. In our patients, better outcomes are shown in trapeziometacarpal joint replacement though, in comparison with resection interposition arthroplasty, the indication criteria for this surgery are limited by factors such as the height of the trapezium bone and bone quality necessary for good osseointegration.
Keywords: Carpometacarpal Joints; Female; osteoartróza; Pain Measurement; palec ruky; Arthroplasty, Replacement; ženské pohlaví; karpometakarpální klouby; artrodéza; přenos šlachy; Tendons; artroplastiky kloubů; lidé; Recovery of Function; Thumb; šlachy; měření bolesti; obnova funkce; Range of Motion, Articular; rozsah kloubních pohybů; Male; Arthrodesis; Trapezium Bone; Osteoarthritis; Joint Prosthesis; protézy kloubů; trapézová kost; mužské pohlaví; Tendon Transfer; Humans